On the trail of ethical responsibility: the historical-philosophical origin and evolution of ethics in social work - Idareta Goldaracena, Francisco (Cuadernos de Trabajo Social, 2013)
The goal of this research paper is to analyze the repercussions that ethical responsibility has had on the Ethics of Social Work from a historical-philosophical perspective. In order to do so, we have divided the article into two sections. The first one has been divided into three parts corresponding to distinct historical time periods: the period between World War I and World War II, the post World War II period and the contemporary period, dating from the 60s until the present times. Each of these parts is composed by a recounting of a historical-philosophical framework consistent with the times, and followed by an explanation of its repercussions on Social Work. Therefore, in each of the three parts, we will revise the conception of responsibility pertaining to each of the aforementioned historical time periods, and the influence they exerted on Social Work. In the second section, we will approximate the Ethics of Emmanuel Levinas towards Social Work, in order to expose the present deep preoccupation for ethical responsibility in the professional practice of Social Work.
Keywords: Ethics; Philosophy; Social Work; E. Lévinas; responsibility